Answer:
Sum of products
Step-by-step explanation:
This is saying a(b + c), and this equals ab + ac so it is a sum of products.
Answer:1/5 is the answer
Step-by-step explanation:
Answer:
Step-by-step explanation:
Add 25 to both sides:
Square root both sides:
(Since a negative number multiplied by itself gives positive, there are two answers.)
Hey there!
The first step we have to do is to add 25 to both sides of the equation.
In our last and final step, we will have to take the square root.
±
We have two answers.
Hope this helps!
The distance from the bottom of the lowest rung to the top of the highest rung 116.7 inch
The unitary method is a technique for solving a problem by first finding the value of a single unit, and then finding the necessary value by multiplying the single unit value.
Given:
Total rungs = 18
distance between rungs = 5.7 inch
thickness = 1.1 inches
So, the distance from the the lowest rung to top of highest rung is
=18* 5.7 + 17* 1.1
=116.7 inch
Learn more about unitary method here:
#SPJ2
An expression relating the distance between the car and motorcycle after t is 52t
Speed of motorcycle = 20 mph
Speed of car = 48 mph
Distance apart after, t hours :
Recall :
Distance traveled = Speed × time
Hence,
Distance traveled by car after t hours
Distance traveled by Motorcycle after t hours
Since, the direction followed by the car and motorcycle forms a right angle, the distance apart after t hours can obtained using Pythagoras :
Recall from Pythagoras :
a² = b² + c²
Where, a = hypotenus
b and c = opposite and adjacent
Therefore, distance apart :
d² = (48t)² + (20t)²
d² = 2304t² + 400t²
d² = 2704t²
Take the square root of both sides :
d = √2704t²
d = 52t
Therefore, the distance between the car and motorcycle after t hours is : 52t
Learn more : brainly.com/question/8283882
Answer:
The middle term of the equation is (x - 4)(x - 3) is -7x .
Step-by-step explanation:
As given the expression in the question be as follow .
= (x - 4)(x - 3)
First open the bracket and simplify the above terms .
= x × x - x × 3 - 4 × x -4 × -3
= x² -3x -4x + 12
= x² -7x + 12
Therefore the middle term of the equation is (x - 4)(x - 3) is -7x .
x^2 - 4x - 3x + 12
= x^2 -7x +12
middle term= -7x